2004
DOI: 10.1111/j.1467-6494.2004.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mothers' Use of Control in Children's Perfectionism: Implications for the Development of Children's Depressive Symptoms

Abstract: The central aim of this research was to investigate the possibility that when parents use heightened control with children, children develop perfectionistic concerns, which may foster depressive symptoms. Mothers' use of control with their elementary school children (N=104) was observed in the laboratory along with their affective expression toward their children; children's behavior (e.g., task engagement) that might influence mothers' use of control was also observed. Self-oriented and socially prescribed pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(95 citation statements)
references
References 68 publications
3
84
0
7
Order By: Relevance
“…Findings of the second regression analysis indicated that negative perfectionism as measured by concern over mistakes, high parental expectations, parental criticism, and doubting of actions subscales was predicted by maternal authoritarian style, neuroticism, and paternal authoritarian style. This findings support previous studies that found correlation between positive perfectionism and authoritative parenting style, openness to experience, and conscientiousness; and correlation between negative perfectionism and authoritarian parenting style and neuroticism (Besharat et al, 2011;Biran & Reese, 2007;Kenney-Benson & Pomerantz, 2005;Rudasill, Adelson, Callahan, Houlihan, & Keizer, 2013). However, the result of this study showed that academically gifted students have different perceptions towards their parents; where maternal parenting style contributes 49.3% to the development of negative perfectionism and paternal parenting style contribute 44.3% to the development of positive perfectionism.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Findings of the second regression analysis indicated that negative perfectionism as measured by concern over mistakes, high parental expectations, parental criticism, and doubting of actions subscales was predicted by maternal authoritarian style, neuroticism, and paternal authoritarian style. This findings support previous studies that found correlation between positive perfectionism and authoritative parenting style, openness to experience, and conscientiousness; and correlation between negative perfectionism and authoritarian parenting style and neuroticism (Besharat et al, 2011;Biran & Reese, 2007;Kenney-Benson & Pomerantz, 2005;Rudasill, Adelson, Callahan, Houlihan, & Keizer, 2013). However, the result of this study showed that academically gifted students have different perceptions towards their parents; where maternal parenting style contributes 49.3% to the development of negative perfectionism and paternal parenting style contribute 44.3% to the development of positive perfectionism.…”
Section: Discussionsupporting
confidence: 82%
“…Researchers abroad have demonstrated the association between parenting styles and perfectionist tendencies in children (Besharat et al, 2011;Biran & Reese, 2007;Flett & Hewitt, 2002;Kenney-Benson & Pomerantz, 2005). Studies found that there were positive correlations between authoritarian parenting style and negative perfectionism, and also between authoritative parenting style and positive perfectionism (SpeirsNeumeister, 2004).…”
Section: Problem Statementmentioning
confidence: 99%
“…Nevertheless, our findings are in line with the idea that parental criticism carries over into NSSI in ED patients through ECP. Past research had identified associations between critical parenting and ECP (McCranie & Bass, 1984) and between critical parenting and psychopathology in children and adolescents (Kenney-Benson & Pomerantz, 2005). Our study was among the first to demonstrate the mediating role of ECP between parental criticism and NSSI.…”
Section: Discussionmentioning
confidence: 72%
“…Further, a number of studies have shown that ECP plays a mediating role in associations between harsh/critical parenting and psychopathology in children and adolescents (Kenney-Benson & Pomerantz, 2005). Similar evidence for this sequence of mediation in the domain of NSSI, however, is inconsistent.…”
Section: Perfectionism and Functions Of Nonsuicidal Self-injurymentioning
confidence: 95%
See 1 more Smart Citation